Pengaruh Keahlian Pelanggan dan Komitmen Afektif Terhadap Kepuasan Melalui Ko-Produksi Pelanggan: Studi Pada Layanan Restoran - Firjatullah, Thoriq Septian; Sanaji (Jurnal Ilmu Manajemen, 2024)
This study aims to determine the effect of customer expertise and affective commitment on satisfaction through customer co-production. It is focused on a restaurant that provides self-service to its customers. This quantitative research uses a descriptive conclusive research design to test 5 hypotheses. The test uses PLS-SEM analysis with 202 respondents. The results showed that all hypotheses were successfully accepted; namely, it was found that customer expertise has a significant effect on co-production, affective commitment has a significant effect on co-production, co-production has a significant effect on customer satisfaction, customer expertise has a significant effect on customer satisfaction, affective commitment has a significant effect on customer satisfaction. From these results, it can be understood that restaurants need to ensure an increase in knowledge for customers and try to develop a sense of affective commitment in customers. With good expertise and a high sense of affective commitment to customers, customers' success in co-production will be higher. This success in co-production creates a sense of satisfaction for customers.